The Impact of Entrepreneurship Orientation, Human Capital, and Social Capital on Innovation Success of Small Firms in East Java - Suyanto, .; Pratono, Aluisius Hery (SBM ITB, 2014)
Abstract. Although entrepreneurship plays an important role on the innovation success of small enterprises, the empirical evidence on this issue is hardly to find. This current study contributes to the empirical finding of innovation success using the case of small firms in East Java. Employing factor analysis and ordinary least squared (OLS) regression, this study finds that entrepreneurship orientation is a key variable affecting innovation success in small firms. Human capital has negative impact on innovation success, while social capital is not a significant contributor on innovation. The implication of these findings closely related to the potential entrepreneurship for developing small firms to medium scales. Keywords: entrepreneurship, innovation success, small firms, human capital, social capital.Abstrak. Meskipun kewirausahaan memainkan peran penting dalam kesuksesan inovasi perusahaan kecil, temuan empiris terhadap hal ini masih sulit ditemukan. Penelitian ini memberikan kontribusi temuan empiris tentang kesuksesan inovasi perusahaan-perusahaan kecil di Jawa Timur. Dengan menggunakan analisis faktor dan regresi ordinary least squared (OLS), penelitian ini menemukan bahwa orientasi kewirausahaan merupakan faktor kunci bagi kesuksesan perusahaan kecil. Modal insani memiliki dampak negatif terhadap kesuksesan inovasi, sementara modal sosial bukan merupakan contributor yang signifikan bagi kesuksesan inovasi. Implikasi dari temuan ini terkait langsung dengan potensi kewirausahaan dalam mengembangkan skala perusahaan dari kecil menjadi menengah.Kata kunci: orientasi kewirausahaan, kesuksesan inovasi, perusahaan kecil, modal insani, modal sosial.